Efecto de la humedad sobre la fertilidad de los huevos de la mosca del mediterráneo, Ceratitis capitata Wied. - Katiyar, K.P.; Ferrer, F. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Artificial plastic lemon molds, artificial orange molds and quart-size polyethylene round freezer jars were used as oviposition sites for the Mediterranean fruit fly, Ceratitis capitata Wied. Plastic lemon and orange molds gave low egg-batch under laboratory conditions of 25°C temperature and 50-60 percent relative humidity when the oviposition period was extended beyond 8 hours. The polyethylene freezer jars gave normal egg-batch up to an oviposition period of 24 hours. The low egg-hatch with lemons or oranges as oviposition sites was due to the desiccation of the eggs inside the molds and not to the toxic effect of the plastic itself. In the polyethylene freezer jars the water collected in the bakelite screw caps in the bottom after they were rinsed maintained a humid atmosphere inside the jars, throughout the oviposition period of 24 hours. Mediterranean fruit fly eggs were incubated at 25°C temperature and 75.5, 85.0, 92.5, 97.5 and 100 percent relative humidities. Low egg-hatch was observed at 75.5 and 85.0 percent relative humidities after 8 hours incubation. Humidities of 92.5 percent or higher gave normal egg-batch up to incubation of 24 hours.